Development of an Android Educational Game Magic Square -Megaforce Assisted to Improve Students' Creative Thinking Skills - Fatahillah, Arif; Wicaksono, Arif; Hussen, Saddam; Setiawani, Susi; Murtikusuma, Randi Pratama (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2023)
Abstract:The development of educational games is very relevant to learning activities in schools today. This research developed the Android educational game Magic Square – Megaforce to be valid, practical, and effective in improving students' creative thinking skills. This research is a development research with a 4-D model. The validity of educational games reached a high category with a correlation coefficient value of 0.95. This educational game is also declared practical with an average learning implementation of 100%. The effectiveness of this educational game was assessed based on classical learning completeness of 85.7%, student learning activities of 80%, and student response questionnaires of 85.5%, all of which were in the Good category. Educational game design can still be refined for further research so that it is more varied.Abstrak:Pengembangan game edukasi sangat relevan dengan kegiatan pembelajaran di sekolah saat ini. Penelitian ini mengembangkan game edukasi Android Magic Square – Megaforce hingga valid, praktis, dan efektif meningkatkan kemampuan berpikir kreatif siswa. Penelitian ini merupakan penelitian pengembangan dengan model 4-D. Validitas game edukasi mencapai kategori tinggi dengan nilai koefisien korelasi 0,95. Game edukasi ini juga dinyatakan praktis dengan rata-rata keterlaksanaan pembelajaran sebesar 100%. Efektifitas game edukasi ini dinilai berdasarkan ketuntasan belajar klasikal sebesar 85,7%, aktivitas belajar siswa sebesar 80% dan angket respon siswa sebesar 85,5% yang semuanya berada pada kategori Baik. Desain game edukasi masih dapat disempurnakan untuk penelitian selanjutnya sehingga lebih variatif.